Analysis and Design of Skybridges connecting Tall Buildings – A case study - Kiriparan, B.; Waduge, B.; Fernando, W.J.B.S.; Mendis, P. (SOCIETY OF STRUCTURAL ENGINEERS, SRI LANKA, 2019)
Skybridges between adjacent tall buildings are generally adopted to offer iconic features such as sky gardens, swimming pools, observation decks and other luxury amenities. Improved fire safety, horizontal connectivity for pedestrians and enhancement of structural performance under lateral loads due to coupling effects are considerable added advantages to the aesthetic superiority. Structural analysis and design of skybridges are paid special attention as tall buildings constantly sway in a random manner under action of wind and earthquake induced lateral loads. The connection configuration between towers and the bridge highly influence the behaviour and design consideration of both towers and skybridge. Although the rigidly connected link provides improved damping and better structural performance under lateral loads resulting from structural coupling effects, alteration in distribution of internal forces through the structural system has to be carefully studied. Members of the towers and skybridge have to be designed to withstand appropriate internal force demands. In contrast, an isolated connection allowing independent movement of skybridge from the towers is convenient for analysis since each structure can be treated separately. However, excessive relative movement of skybridge causing human discomfort is inevitable in that case. Further, special attention has to be paid in selection of suitable structural bearings such as elastomeric, friction pendulum, guided slide bearing or a customized combination to achieve intended isolation mechanism. Thus selection of most suitable configuration of the connectors is vital. In addition, aerodynamic performance of the bridge pertaining to stability and human comfort under different wind conditions has to be verified. Requirement of auxiliary damping devices to meet human comfort of the skybridge has to be investigated. This paper addresses such fundamental design considerations in detail through a case study of a skybridge connecting fifty storied twin towers, authors have designed. Insight for connection mechanism of links connecting high rise towers, analysis of linked tall buildings under lateral loads, design of viscous dampers to improve the performance of isolated skybridges and aerodynamic effects on skybridge design are discussed.
Keywords: Skybridges; Linked tall buildings; Bearings; Viscous dampers; Structural coupling